Double umbilical cord blood transplant is effective therapy for relapsed or refractory Hodgkin lymphoma. Issue 7 (2nd July 2016) - Thompson, Philip A.; Perera, Travis; Marin, David; Oran, Betul; Popat, Uday; Qazilbash, Muzaffar; Shah, Nina; Parmar, Simrit; Rezvani, Katayoun; Olson, Amanda; Kebriaei, Partow; Anderlini, Paolo; et al.
Abstract: A sub-group of patients with Hodgkin Lymphoma (HL) who relapse after autologous stem cell transplant can achieve long-term disease-free-survival after allogeneic stem cell transplant (alloSCT). There is limited information regarding the tolerability and efficacy of double umbilical cord blood transplant (dUCBT) for relapsed/refractory HL. We analyzed 27 consecutive, heavily pre-treated patients receiving dUCBT for relapsed/refractory HL at two centers from 2003–2014. The majority of patients relapsed <6 months after autologous stem cell transplant. A total of 15 patients received myeloablative (most commonly melphalan, fludarabine, thiotepa and anti-thymocyte globulin [ATG]) and 12 non-myeloablative conditioning regimens (fludarabine, cyclophosphamide, 200cGy total body irradiation +/- ATG). All patients engrafted; median time to neutrophil and platelet engraftment was 17 and 37 days, respectively. Overall response rate was 68%; 58% achieved complete remission. Median progression-free survival (PFS) was 12.2 months; median overall survival was 27 months. Cumulative incidences of relapse and of non-relapse mortality at 5 years were 30% and 37.9%, respectively; 5-year PFS was 31.3% (95%CI 10.1–52.5). There was a trend toward inferior PFS in patients with lymph node size ≥2 cm at the time of alloSCT ( p = 0.07) and toward inferior survival in patients with chemorefractory disease pre-alloSCT ( p = 0.12). dUCBT is feasible in patients with heavily pre-treated HL and can achieve long-term disease-free survival in approximately 30% of patients.